Learning Management Model in Improving Student Worship Implementation Competency - Nur Sakinah (Al-Ulum: Jurnal Pendidikan Islam, 2020)
The purpose of this research is to find out the learning management model in increasing students' religious competence. The research method used is a qualitative research method, with the type of field research. There are three collection techniques used in this study, namely: interviews, observation, and documentation. Data analysis carried out in this study used data analysis with the Miles & Huberman interactive analysis model, which was carried out through four steps, namely collecting data, selecting data, presenting data, drawing conclusions and verifying. To guarantee the validity of the data, triangulation techniques are used. The results found that the model used in worship learning activities is using the POAC model, with the following stages: First, planning activities, namely by setting targets to be achieved and the strategies used in carrying out these learning activities; Second, Organizing Activities, namely schools making arrangements for the resources they have and making arrangements related to learning activity procedures; Third, Actualization of activities, namely learning activities carried out in accordance with planned and regulated procedures; Fourth, to control, namely to supervise all learning activities carried out.